Kurbak doitzea / diseinu nagusia, Michael Dubson, Amanda McGarry; software-garapena, Michael Dubson ...[et al.]; itzulpena,José Manuel López Irastorza - Dubson, Michael; Dubson, Michael; McGarry, Amanda; López Irastorza, José Manuel
Kurbak doitzearen inguruko simulazio interaktiboa.